Application of extracellular vesicles proteins in cancer diagnosis - Huang, Defa; Rao, Dingyu; Xi, Xuxiang; Zhang, Zuxiong; Zhong, Tianyu (Frontiers in Cell and Developmental Biology, 2022)
Early tumor diagnosis is crucial for its treatment and reduction of death, with effective tumor biomarkers being important tools. Extracellular vesicles (EVs) are small vesicles secreted by cells with various biomolecules, including proteins, nucleic acids, and lipids. They harbor a double membrane structure. Previous studies on EVs in cancer diagnosis and therapy focused on miRNAs. Nonetheless, EVs contain proteins that represent physiological and pathological state of their parental cells. EVs proteins can reflect the pathological state of some diseases, which provides a basis for diagnosis and treatment. This study describes the role of EVs in cancer and summarizes the use of EVs proteins as diagnostic markers in different cancer types. Specifically, we discuss the potential and shortcomings of EVs as tumor biomarkers.